Pengaruh Kredit Macet dan Penyaluran Kredit Terhadap Stabilitas Keuangan PT. BCA Tbk Tahun 2015-2024 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study to analyze the effect of Non-Performing Loans (NPL) and Loan Growth on the financial stability of PT Bank Cental Asia Tbk during 2015-2024 period. Financial stability in this study is measured using two main indicarors: the Capital Adequancy Ratio (CAR) and Return on Assets (ROA). The research adopts a quantitative appoarch using multiple linear regresion analysis. The result indicate the partially, NPL has a positive and significant effect oon CAR, qhile Loan Growth does not signifivantly affect CAR. Conversely, NPL has a significant negative effect on ROA, and Loan Growth has a significant positive effect on ROA. Simultaneously, both indipendent variabels NPL and Loan Growth have a significant effect on both CAR and ROA. These findings highlight that effective credit risk management and well executed lending strategies are crucial in maintaining the bank’s financial stability and profitability.